Effect of penetration enhancers on the permeability characteristics of lisinopril transdermal delivery systems - Chathoth, Suja; Ramasami, C.; Rompicharla, Narayanacharyulu (Asian Journal of Pharmaceutics (AJP), 2014)
Lisinopril is an ACE inhibitor used in the treatment of hypertension and heart failure, prophylactically after myocardial infarction and in diabetic nephropathy. Lisinopril is slowly and incompletely absorbed following oral administration. On an average about 25% of the drug is absorbed after administration of a single dose.Thus, a controlled drug delivery formulation of lisinopril for transdermal absorption would be more advantageous and beneficial for improving the bioavailability and reducing the frequency of administration for long-term treatment. Matrix type transdermal films were prepared by solvent casting technique using a combination of ammonia methacrylate copolymer, type A. USP/NF( EudragitRL100) and poly vinyl pyrrolidone (PVP) as polymers. Propylene glycol was used as plasticizer. Glycerine, dimethyl sulphoxide (DMSO) and span-60 were used as penetration enhancers. The physicochemical parameters like thickness, folding endurance, drug content, tensile strength and stability were evaluated. In- vitro drug release and in-vitro skin permeation studies were carried out using modified Keshary-Chien permeation cell. Infra-red spectroscopy (IR) and differential scanning colorimetry (DSC) were performed to follow drug carrier interactions. In- vitro drug permeation profile of the formulated films showed that formulations containing span-60 as penetration enhancer (F4, F8, F12, F16, F20) showed highest drug permeation. From the results of this study it indicated that the permeation of lisinopril from films containing span-60 as penetration enhancer was the best at all polymer ratios as compared to the films containing DMSO and glycerine. The order of permeability enhancement from the films was found to be span-60 > DMSO > glycerine. There was no significant difference in the physicochemical characters and drug content for a period of 3 months.